Witnessing Economic Growth in Kazakhstan through Sustainability and Manufacturing Performance: Mediating Role of Supply Chain Performance - Thaniya Pongsiri; Sriparinya Toopgajank; Boonsri Suteerachai; Arifeen Yama (International Journal of Supply Chain Management, 2020)
At the present time, a number of organizations consider the implementation of sustainable activities as not just a competitive gain however as well as a requirement for enduring existence. Thus, it is vital that the researcher comprise the factor of sustainability in assessing the performance of the supply chain of an organization. But very little investigations have examined the influence of sustainability and manufacturing on economic growth, with the mediating impact of supply chain performance. The existing article demonstrates a unique methodology for assessing the performance of the supply, which could be utilized by Kazakh manufacturing companies. Relied on the past studies and on the opinions of the experts, the researcher recognized the functions of the supply chain which impact the supply chain, sustainability and manufacturing performance, and the economic growth. In this study, the scholar of this study designed a survey-based questionnaire and surveyed the experts of the manufacturing organizations. Total of 267 participants filled out the survey. The results of this study show that all the research hypotheses of the study are accepted.